Biofuel from microbes and plants green energy alternative - Kumar, Nitish (CRC Press, an imprint of the Taylor & Francis Group, 2022)
"Global concern for energy security and environmental protection has put great emphasis on the search for alternative energy sources, particularly for the transport sector. Biofuels have emerged as a highly promising source of alternative energy, and have drawn global R&D for their production using biomass. With the increasing worldwide demand of energy along with the depletion of conventional fossil fuel reserves, there has been growing global interest in developing alternative sources of energy. There has also been concern in growing economies regarding energy security. Biofuels offer much promise on these frontiers. In addition to the above, they also have a reduced environmental impact in comparison to fossil fuels. Biofuels provides state-of-the-art information on the status of biofuel production and related aspects. Academics, researchers, engineers and technologists will develop a greater understanding of the relevant concepts and solutions to the global issues related to achieving alternative energy application for future energy security, as well as environmental sustainability in medium and large-scale industries. Key Features Detailed overview of the alternative energy field and the role of biofuels as new energy sources Gives a detailed account of the production of biodiesel from non conventional bio-feedstocks such as algae, microbes and vegetable oils Recent updates about biotechnological improvement of plant and microbial source for biofuel production"--Provided by publisher.